La zone d’activités économiques : objet urbain non identifié ? - Patricia Lejoux; Corentin Charieau (Territoire en Mouvement)
The aim of this paper is to explore the visibility and invisibility of economic activity zones in urban planning. It sheds light on a paradox: economic activity zones are not considered by urban scholars nor urban practitioners as a stake, whereas they take part in urban dynamics. Three reasons explain this invisibility: economic activity zones are more considered as an economic object than an urban object; they are associated with the Functionalist approach which is rejected by urban planners; the contribution of economic activities to suburbanization is underestimated compared to housing. Making economic activity zones more visible could be an important issue for scholars as well as practitioners in urban planning. It could highlight new urban dynamics as the role of economic activities in urban sprawl, the stake of urban quality in suburban areas and the ways to govern the implementation of economic activities in suburban areas.